Finance and Development, December 1986. (Finance and Development; Finance and Development ;, 1986)
This paper describes the World Bank's mission in a changing world. Conditionality of the Bank is different in several ways as it operates over a longer timeframe and relates to the more comfortable issues of economic growth rather than financial stabilization. The longer timeframes of the Bank's programs require reaching agreement with borrowing countries on the desirability of maintaining the course that's being advocated for an extended period. Many developing countries are unduly sensitive about the possibility that they may have to exercise their sovereignty more forcefully in the future.